Representações do mundo do trabalho: o lugar do SINE no imaginário dos desempregados de Santa Maria - RS - Rodrigues, Ana Paula de Lima (2010)
The aim of this master s dissertation is to identify the social representations constructed around the institution SINE in Santa Maria, having as the main source reports from social actors who frequent this place in search for jobs. It basically intends to understand how the social imaginary takes this institution as one of the main interlocutors with labor world in Santa Maria and as an agency that manages and performs actions of market insertion. Then, this study aims to learn how actors experience this relationship and the meaning they attribute to their actions, having as reference political and institutional practices mirrored by SINE. It intends to rescue the several meanings that people excluded from formal market place have about labor world and the relation with their biographies and their different insertions in the social contexts they are. From this universe of meanings it infers that people establish action plans in their daily routine in relation to labor world and their insertions in it. It highlights that this first view of people about labor world and the place and role of SINE in this context is important because it is a diagnosis not only of the restrict labor world but also of the political world as well as of the status and classes structures in which they are inserted. The contents are linked: basic reasons, such as economic survival with visions about the functioning of the political world. SINE itself constitutes an entity which conserves in its nature and routine these two dimensions to be an organism of (economical) labor managing while it maintains deep connections to the world of politics. The conclusions of the study come from qualitative analysis of semi-structured interviews applied in November, 2009.